Study of Reversible Ion-Isotopic Self Diffusion Reaction Kinetics Using 82Br as a Radioactive Tracer Isotope - LOKHANDE, R.S.; SINGARE, P.U. (Asian Journal of Chemistry, 2010)
Radioactive tracers as a sensitive analytical technique have been used to study the reversible ion-isotopic self-diffusion reactions. In forward self-diffusion reactions, the ion exchangers in bromide form were equilibrated with bromide ion solution (labelled with 82Br as a radioactive tracer isotope) in the concentration range of 0.005-0.100 M. In reverse ion-isotopic self-diffusion reactions, the labelled ion exchangers in the range of 0.7500-1.2500 g were equilibrated with 0.0100 M bromide ion solution concentration. The results of reversible ion-isotopic self-diffusion reaction indicate that under identical experimental parameters, the reaction rates (in min-1) are calculated to be nearly same, indicating that forward and reverse ion-isotopic self-diffusion reactions are complementary to each other.